Iridium- and rhodium-catalyzed C–H activation and formyl arylation of benzaldehydes under chelation-assistance. Issue 23 (25th May 2016) - Yang, Xifa; Wang, He; Zhou, Xukai; Li, Xingwei
Abstract : Mild and efficient synthesis of benzophenones via Ir(iii )- and Rh(iii )-catalyzed, directing group-assisted formyl C–H arylation of benzaldehydes has been achieved using diaryliodonium salts, in which Rh(iii ) and Ir(iii ) catalysts exhibited a complementary substrate scope. Abstract : Mild and efficient synthesis of benzophenones via Ir(iii )- and Rh(iii )-catalyzed, directing group-assisted formyl C–H arylation of benzaldehydes has been achieved using diaryliodonium salts, in which Rh(iii ) and Ir(iii ) catalysts exhibited a complementary substrate scope.